PENYELESAIAN PEMBIAYAAN BERMASALAH PADA PEMBIAYAAN MURABAHAH DENGAN TANGGUNGRENTENG DI BTPN SYARI’AH KCP CIKAMPEK - Kurnilawati, Iis Dewi; Fatoni, Siti Nur (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2019)
ABSTRACTMurabahah financing agreement conducted by the National Pension Savings Bank of sharia Cikampek auxiliary Branch Office is murabahah financing for the purchase of business capital of a group of rural women who want to expand their business. Over time there are some among the customers who do not meet the achievements by not installing on time and even experiencing a payment jam. To solve the financing problems, the bank implements a joint responsibility system or financing in groups. The purpose of this study is to know (1) the implementation of murabahah financing with joint responsibility in the National Pension Savings Bank of sharia Cikampek auxiliary Branch Office, (2) the settlement of problem financing in murabahah financing with the joint liability of the National Pension Savings Bank of sharia Cikampek auxiliary Branch Office, (3) the relevance of the settlement of non-performing financing on murabahah financing with joint liability at the National Pension Savings Bank of sharia Cikampek auxiliary Branch Office with muamalah fiqalah. Murabahah financing with joint responsibility is financing conducted in groups, this financing provides convenience to customers who want to expand their business but he does not have access to the bank. In this financing the customer does not have to provide an assurance of the object because the collateral used is a guarantee of self or trust between the bank and the customer. The method used is descriptive method of applying, describing, and describing the implementation of joint responsibility at murabahah financing in the National Pension Savings Bank of sharia Cikampek auxiliary Branch Office. The data collection techniques through interviews to the bank and its customers. Observation by way of observation directly to the field. The study of literature in the form of books made into literature in this study, as well as data sources obtained from various references in the form of notes, papers, dissertations and others related to the object under study. Based on the results of the research, it is found that in the implementation of murabahah financing with joint responsibility there are several stages: (1) financing proposal, (2) basic training of membership, (3) financing contract, (4) group savings, (5) Groups and group leaders. The problematic financing settlement is done by prevention of problem financing and when problematic financing still occurs, the settlement will be used using the joint responsibility system, customer savings fund, family approach, and rescheduling policy. Settlement of problem financing conducted by the National Pension Savings Bank of sharia Cikampek auxiliary Branch Office Assistant in murabahah financing with joint responsibility is not yet relevant to muamalah fikih for violating the principle of jurisprudence muamalah namely the principle of an ta 'ra din.